2021
DOI: 10.1007/s00299-021-02671-y
|View full text |Cite
|
Sign up to set email alerts
|

Agroinfiltration for transient gene expression and characterisation of fungal pathogen effectors in cool-season grain legume hosts

Abstract: Key message Modified pEAQ-HT-DEST1 vectors were used for agroinfiltration in legumes. We demonstrate protein expression and export in pea, lentil, and faba bean; however, the method for chickpea was not successful. Abstract Agroinfiltration is a valuable research method for investigating virulence and avirulence effector proteins from pathogens and pests, where heterologous effector proteins are transiently expressed in plant leaves and hypersensitive necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Besides, GUS activity in transgenic chrysanthemums using the CaMV35S promoter was low [ 55 ]. Similar results were also observed in chickpea [ 56 ]. Notably, along with the rapid development of DNA assembly technologies, multigene transformation which has the ability to introduce more complex and ambitious phenotypes into transgenic plants, is becoming more and more frequently-used in plant biotechnology [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…Besides, GUS activity in transgenic chrysanthemums using the CaMV35S promoter was low [ 55 ]. Similar results were also observed in chickpea [ 56 ]. Notably, along with the rapid development of DNA assembly technologies, multigene transformation which has the ability to introduce more complex and ambitious phenotypes into transgenic plants, is becoming more and more frequently-used in plant biotechnology [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…This method may also be an alternative for researchers who struggle with expressing SCR effectors using microbial expression systems. In line with this, a recent study showed that using agroinfiltration, the apoplast targeted NLP2 (necrosis and ethylene-inducing peptide-like protein) from Peyronellaea pinodes was successfully expressed and induced necrosis in legume plants including field pea, faba bean and lentil, but not in chickpea (Debler et al, 2021). This further corroborates that plants can serve as a heterologous expression system to produce biologically active fungal effectors in secreted form.…”
Section: Discussionsupporting
confidence: 63%
“…The host cultivar responses shown are representative of at least three replicates and additional images for other replicates are provided in Figure S5. Agroinfiltration with a negative control, green fluorescent protein (GFP), and a positive necrosis control, necrosis-inducing effector nep1-like protein (NLP) (Bailey, 1995;Debler et al, 2021), produced the expected responses in the lentil cultivars tested. (P94-24) and AlAvr1-2 (AlKewell).…”
Section: Functional Characterization Of G2688 Suggests the P94-24 Iso...mentioning
confidence: 99%
“…To test the functional properties of the AlAvr1 effector biparental population trait-associated locus, we developed constructs based on the pEAQ-HT vector (Sainsbury & Lomonossoff, 2008;Sainsbury et al, 2009) for transient expression in lentil using agroinfiltration as described by Debler et al (2021). Vector diagrams are shown in Three-week-old lentil plants were infiltrated with Agrobacterium suspension at the adaxial leaf surface using a 1-ml plastic syringe.…”
Section: Functional Characterization Of the G2688 Effector Using Agro...mentioning
confidence: 99%
See 1 more Smart Citation